Acoustic/mechanical properties of polyurethane composites with syntactic hollow spheres. (30th November 2020) - Jiang, Fengchun; Yu, Tianmiao; Wang, Chunhe; Cao, Mengxin; Wang, Zhenqiang; Chang, Yunpeng; Guo, Chunhuan
Abstract: In this investigation, a variety of polyurethane composites with different syntactic hollow spheres were prepared by casting method, using 316 L stainless steel hollow spheres and 316 L stainless steel–Al2 O3 double‐layer hollow spheres as reinforcements. The sound insulation and absorption properties of polyurethane composites with different syntactic hollow spheres were tested by impedance tube. The effects of the hollow spheres on the acoustic properties of composites were analyzed and compared with polyurethane resin and polyurethane/solid spheres composites. The experimental results reveal that the sound transmission loss of polyurethane can be improved by the addition of hollow spheres, and the range of sound absorption frequency of polyurethane tends to move to lower frequency. Otherwise, the sound insulation and absorption frequency range of polyurethane can be broadened by the effect of 316 L stainless steel–Al2 O3 double‐layer hollow spheres. In addition, the compressive strength and stiffness of polyurethane composites have been significantly improved after hollow spheres added. Comparing with polyurethane, the compressive strength and stiffness of PU/316 L–Al2 O3 HS increased by 47.9% and 115.9%, respectively.